Экономика связи: учебник - Фирсова С. М. Софья Михайловна; Цатурова Р. Г. Раиса Гарникова; Ковалгина Т. М. Тамара Михайловна; Горелик М. А. Мусиана Александровна (Москва, Радио и связь, 1984)
Авт. указаны на обороте тит. л.